(3GdGfJUGQ Ydi YdeGA GdCeUGQ aj JbQjQ GdeNJGQ ef cdGe GdCFeI hcdGe YdeGA GdCeI aj GdeSGFd GdabgjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdHGH GdSGOS ai GdhVhA , hPcQ NUGFUI s
(3BNQgG (B:s
(3jfJgi HfgGjI HGH GdZSd , hBNQg bhdg (B: (3Yf GdfHi Udi Gddg Ydjg hSde Cfg bGd (B: (3jG Ydi , ef CWGY CeQCJg ai CQHY cHg Gddg Ydi hLgg ai GdfGQ , ai GdPgGH Edi GdMeGeGJ , hGdYQSGJ , hGdefGMGJ hdHS GdKjGH GdQbGb s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdgOhjI (B138) s
Keywords: (3abg GdePGgH GdCNQis